Students’ Reading Comprehension Literacy in Indonesian Language Learning: A Systematic Literature Review of Factors, Impacts, and Intervention Strategies - Figo Fajar Aprian; Nurlaksana Eko Rusminto; Munaris; Sumarti; Siti Samhati (ISEJ : Indonesian Science Education Journal, 2025)
This research aims to examine the problem of low reading comprehension literacy in Indonesian language learning at school. This study is expected to identify various factors causing and impacting low reading comprehension literacy, as well as research-based solutions that provide theoretical and practical contributions to the development of more effective Indonesian language learning in improving students' reading comprehension literacy. This research method uses a library study or systematic literature review approach. Based on the analysis and discussion of literary materials, low reading comprehension literacy is a systemic and multidimensional problem. This problem is manifested from two main perspectives: international comparative data and national assessment data. Both internal and external factors contribute to low reading comprehension literacy. The impact of low reading comprehension literacy is on students' academic achievement in Indonesian language learning and on a much broader and more comprehensive essence. Various efforts have been made and proven effective in improving reading comprehension literacy.